World under Revision The Poetry of Wis?awa Szymborska - Nycz, Ryszard; Nycz, Ryszard; Ligeza, Wojciech (Peter Lang, 2019)
This book provides a comprehensive overview of the entirety of Wislawa Szymborska's poetic oeuvre. The author employs in-depth historical reflection on Szymborska's beginnings to reveal that without describing her post-war beginnings and reflecting on her early entanglement in socialist realist newspeak Szymborska's mature anti-dogmatic attitude will remain unclear. The book shows how Szymborska's rhetoric and stylistics figures of reservation, negation, contradiction, tautology, and repetition are closely connected with the construction of the poetic world and affect the shape of her messages. After all, Wislawa Szymborska is a poet of sophisticated wit, a surprising freedom of expression, and an unusual game with various literary styles, even with colloquial Polish.